Fluvial influx and weathering history of the Himalayas since Last Glacial Maxima - Isotopic, sedimentological and magnetic records from the Bay of Bengal - Chauhan, O.S.; Patil, S.K.; Suneethi, J. (My University, 2004)
From temporal variations in stable isotopes, mineral magnetism, clay minerals and granulometric parameters from a sup(14) C dated core have been used to understand weathering history and influence of climate on the terrigenous fluxes into the Bay of Bengal. Well defined events of reduced fluvial influx are deduced at 20-15, 12.7, 9.5, approx. 5-4.3 and 1.8-2.2 Ka BP and at least two major fluvial pulses initiated around 11.5 and 9.5 Ka PB. The intensified monsoon regime appeared to have set in at around 9.5 Ka, and had pauses at approx. 5 and 2.2 Ka BP during the Holocene. The climatic variability appeared to have significant control over characteristics of terrigenous flux into the bay, particularly during the glaciation events. Illite, chlorite, smectite and kaolinite are the clays present in the core. From the abundance of chlorite (the clays produced in arid cold climate) and increased contents of silt, a reduced chemical weathering during events of glaciations has been inferred. Occurrence of coarser magnetic grains in the lower levels of the cores (35-100 cm), perhaps, suggests higher magnitude of physical weathering in Pre-Holocene in the Hinterland. An intensified chemical weathering in the Himalayas, under an active summer monsoon regime after 9.5 Ka BP, appears to have enhanced fluxes of finer magnetic minerals, clay size detritus and reduced chlorite during the entire Holocene (0-30 cm levels).
Keywords: Sedimentological; Fluvial influx; Glacial maxima - Isotopic; Clay minerals; Magnetic minerals